A Prototype Knowledge-Based System for Ceramic Matrix Composites Material Selection of Automotive Engine Components - Devanesan Jacob, M. Suresh (2002)
The aim of this research project is to develop prototype knowledge based system for ceramic matrix composites of automotive engine components. The materials are selected from ceramic matrix composites. The selected materials will be able to increase the efficiency of an engine and reduce weight. The designed knowledge based system consists of a knowledge based, material database and product design parameters. The development of such expert system for ceramic matrix composites leads to further increase in their application in high temperature field. The proposed system helps to select the suitable materials for automobile engme components. The materials chosen for the research are ceramic matrix composites. For selecting materials to engine components, few specifications are laid out as constraints in tenus of rule conditions. The materials, which satisfy the conditions, are selected as suitable materials. The rules based reasomng are used to select the materials. For different range of constraint values, the selected materials will vary. As for as constraint values are concerned, the values are selected from the product design specifications. The product design specifications are chosen from the past design and are calculated from the design procedures. The selected materials are ranked according to the properties and stored as result. The most suitable material is labeled as best material and the next level of materials are ranked according to the properties